World Water Day 2012. "Water and Food Security: The World is Thirsty Because We are Hungry". (1st January 2011) - Quagliarotti, Desiree
The World Water Day held in 2012 focused on the link between water use and food production. Today the challenge is to meet the nutritional needs of a growing world population in a context of natural resource scarcity. The world population is predicted to grow from 7 billion in 2011 to 8.3 billion in 2030 and 9.1 billion in 2050. Consequently, by 2030 food demand is predicted to increase by 50 percent. In this context, water is a strategic variable since it is an increasingly scarce resource and one of the fundamental input factors in food production. For example, the average person drinks about 2.5 litres of water a day, about 1500 litres of water are required to produce 1 kilogram of wheat, and 10 times more to produce 1 kilogram of beef. Producing feed crops for livestock, slaughtering and meat processing, and extracting and producing milk and other dairy products require large quantities of water. Th e booming demand for livestock products is increasing the demand for water at every stage along the livestock value chain. The aim of this year's World Water Day was thus to open an international debate in order to identify strategic choices capable of combining, globally and locally, the objective of food security with that of water resource protection.